MOBILE JOURNALISM APPLICATIONS AND THEIR IMPACT ON DEVELOPING MEDIA SKILLS AMONG UNIVERSITY STUDENTS - Mohammed Rashid Majeed; Ali Falih Dakhil Al-Karim (Scholars Digest Publishing, 2025)
This research aims to study the use of mobile journalism among university students and to reveal the extent to which it impacts the development of their media skills in a rapidly evolving digital media environment. The technological advancements in smartphones and their applications have contributed to a radical change in the methods of news gathering, content production, editing, and publication, providing students with extensive capabilities to produce multimedia media materials easily and quickly compared to traditional methods. The study's central question is: To what extent do university students utilize mobile journalism, and what is its impact on developing their media skills? This study adopted a descriptive and survey methodology as the most suitable approach for analyzing the phenomenon and monitoring students' trends in using smartphone applications for producing, editing, and distributing media content. The study was conducted with students at the College of Media at Thi-Qar University from December 2023 to March 2024. Previous studies concluded that mobile journalism has become an essential tool in the modern media industry due to its speed, immediacy, and interactivity, as well as its ability to integrate filming, editing, and broadcasting processes into a single device. The literature also highlighted its role in developing communication skills, content creation, and supporting professional media practice. The research concludes that students' use of mobile journalism significantly contributes to enhancing their media skills, particularly in online editing, audiovisual content production, audience engagement, and distributing media content via digital networks. This makes it an effective tool for training and preparing students for the demands of the modern media job market.
Keywords: Mobile journalism, media skills, smartphone applications, digital media, university students.